PD-L1 and tumor-infiltrating CD8+ lymphocytes are correlated with clinical characteristics in pediatric and adolescent pituitary adenomas - Shi, Mengwu; Song, Yifu; Zhang, Yaochuan; Li, Longjie; Yu, Juanhan; Hou, Ana; Han, Sheng (Frontiers in Endocrinology, 2023)
Objective To investigate the levels of tumor-infiltrating CD8+ lymphocytes (CD8+ TILs) and the expression of programmed cell death receptor ligand 1 (PD-L1) in the tumor microenvironment (TME) of pediatric and adolescent pituitary adenomas (PAPAs) and analyze the correlation between their levels and the clinical characteristics. Methods A series of 43 PAPAs cases over five years were enrolled. To compare the TME of PAPAs and adult PAs, 43 PAPAs cases were matched with 60 adult PAs cases (30 cases were between 20-40 years and 30 cases were older than 40 years) for main clinical characteristics. We detected the expression of immune markers in PAPAs by immunohistochemistry and analyzed their correlation with the clinical outcomes using statistical methods. Results In the PAPAs group, CD8+ TILs level was significantly lower (3.4 ± 5.7 vs. 6.1 ± 8.5, P=0.001), and PD-L1 expression (0.040 ± 0.022 vs. 0.024 ± 0.024, P<0.0001) was significantly higher as compared with the older group. The level of CD8+ TILs was negatively correlated with the expression of PD-L1 (r=-0.312, P=0.042). Moreover, CD8+ TILs and PD-L1 levels were associated with Hardy (CD8: P=0.014; PD-L1: P=0.018) and Knosp (CD8: P=0.02; PD-L1: P=0.017) classification. CD8+ TILs level was associated with high-risk adenomas (P=0.015). And CD8+ TILs level (HR=0.047, 95% CI 0.003-0.632, P=0.021) was correlated with the recurrence of PAPAs. Conclusion Compared with adult PAs, the TME in PAPAs expresses a significantly altered level of CD8+ TILs and PD-L1. In PAPAs, CD8+ TILs and PD-L1 levels are associated with clinical characteristics.